2017
DOI: 10.2147/cia.s127023
|View full text |Cite
|
Sign up to set email alerts
|

The effect of visual biofeedback on balance in elderly population: a systematic review

Abstract: Background: Balance is commonly affected by multiple factors, especially among the elderly population. Visual biofeedback (VBF) is an intervention tool that can be used in balance rehabilitation. Aim: This study aimed to systematically review randomized controlled trials that examine whether VBF training is effective in improving balance in an elderly population. Data sources: Three databases were searched: CIAHL, EMBASE, and MEDLINE. The searches were limited to the period from 2010 to 2016. Eligibility crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 25 publications
(130 reference statements)
1
18
0
Order By: Relevance
“…Studies comparing the effectiveness of conventional physical therapy to Wii Fit balance training in older adults and persons with unilateral peripheral vestibular hypofunction found that balance training with virtual reality alone was not superior to traditional balance therapy ( 83 , 84 ). Based on a recent systematic review, there is moderate evidence that visual feedback is beneficial in older adults with balance impairment ( 85 ). One study showed no overall benefit of balance training in healthy older adults when training was performed both with and without multimodal (vibrotactile, auditory, and visual) SA ( 86 ).…”
Section: Rehabilitation Using Augmented Sensory Feedbackmentioning
confidence: 99%
“…Studies comparing the effectiveness of conventional physical therapy to Wii Fit balance training in older adults and persons with unilateral peripheral vestibular hypofunction found that balance training with virtual reality alone was not superior to traditional balance therapy ( 83 , 84 ). Based on a recent systematic review, there is moderate evidence that visual feedback is beneficial in older adults with balance impairment ( 85 ). One study showed no overall benefit of balance training in healthy older adults when training was performed both with and without multimodal (vibrotactile, auditory, and visual) SA ( 86 ).…”
Section: Rehabilitation Using Augmented Sensory Feedbackmentioning
confidence: 99%
“…There is a need to create intervention programs to improve balance and muscle strength that can reduce the number of falls while also restoring quality of life in seniors ( Weber et al, 2018 ). Several studies investigated the effects of exercise using visual biofeedback as an intervention tool that can be used in balance rehabilitation ( Alhasan et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of biofeedback provides individuals with additional information about their performance, allowing them to develop changes in their behavior or posture, which could potentially lead to better performance of the tasks. In the literature, evidence exists supporting the integration of visual biofeedback in the balance training programs, as this provides additional benefits compared to traditional exercise programs or no intervention [22].…”
Section: Introductionmentioning
confidence: 99%